Steel for cold working and its manufacturing method

JP7643996B2Active Publication Date: 2025-03-11KOBE STEEL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021209428
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2021-12-23
Publication Date
2025-03-11
Estimated Expiration
2041-12-23

AI Technical Summary

Benefits of technology

【0016】 本発明の1つの実施形態では、比較的低い球状化焼鈍温度で従来と比べ明らかに短い球状化焼鈍時間であっても十分に軟質化することができる冷間加工用機械構造用鋼およびその製造を提供することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643996000004
    Figure 0007643996000004
  • Figure 0007643996000005
    Figure 0007643996000005
  • Figure 0007643996000001
    Figure 0007643996000001
Patent Text Reader

Abstract

To provide a machine structural steel for cold working capable of sufficiently softening even when a spheroidizing time is shortened in a relatively low spheroidization annealing temperature and a manufacturing method thereof.SOLUTION: A machine structural steel for cold working comprising: C: 0.30 to 0.45 mass%, Si: 0.10 to 0.40 mass%, Mn: 0.50 to 1.00 mass%, P: 0.050 mass% or less, S: 0.050 mass% or less, Cr: 0.80 to 1.30 mass%, Al: 0.01 to 0.10 mass%, balance: iron and inevitable impurities, and having an area ratio of proeutectoid ferrite of 10% or more to 70% or less, and containing one or more selected from the group consisting of bainite, martensite and pearlite, and having a dislocation density of 3.5×1014 m-2 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to cold work mechanical structural steel and a method for producing the same. [Background technology]

[0002] In manufacturing various parts such as automobile parts and construction machine parts, hot-rolled materials such as carbon steel or alloy steel are often subjected to spheroidizing annealing in order to impart cold workability. The rolled material, whose cold workability has been improved by spheroidizing annealing, is then cold worked, and if necessary, further machined such as cutting, formed into a predetermined shape, and then quenched and tempered for final strength adjustment.

[0003] In recent years, the conditions for spheroidizing annealing have been reviewed from the viewpoint of energy saving, and in particular, there is a demand for shortening the time for spheroidizing annealing. If the processing time for spheroidizing annealing can be reduced, it is expected that the amount of energy consumption and CO2 emissions can be reduced accordingly.

[0004] However, when a conventionally known hot-rolled material is used and the time of spheroidizing annealing treatment (hereinafter sometimes referred to as "spheroidizing annealing time") is significantly shortened, it is known that the spheroidizing degree, which is an index of the degree of spheroidization of cementite, deteriorates, making it difficult to sufficiently soften the steel and deteriorating the cold workability, and therefore it is not easy to shorten the spheroidizing annealing time. Therefore, techniques for sufficiently softening the steel even when the spheroidizing annealing time is shortened are being studied.

[0005] For example, Patent Document 1 discloses a steel for machine structural use that can ensure cold formability even when the spheroidizing annealing time is shortened by setting the area ratio of pro-eutectoid ferrite to 30% or more and 70% or less and setting the average grain size of ferrite crystal grains to 5 to 15 μm in a rolled material having a specified composition. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-125538 A Summary of the Invention [Problem to be solved by the invention]

[0007] By using the steel for machine structural use described in Patent Document 1, the spheroidizing annealing time (the total of the holding time at a predetermined holding temperature and the cooling time from the holding temperature to a predetermined air-cooling start temperature), which previously required about 15 hours, can be shortened to about 10 hours. However, there is an ever-increasing demand for shorter spheroidizing annealing times, and there has been a problem in that the use of the steel for machine structural use described in Patent Document 1 does not meet this demand.

[0008] The present invention has been made in view of the above circumstances, and aims to provide a steel for machine structural use for cold working, which can be sufficiently softened even if the spheroidizing treatment time is clearly shorter than the conventional time, for example, significantly shorter than 10 hours, at a relatively low spheroidizing annealing temperature, for example, about 750°C, and a method for manufacturing the same. [Means for solving the problem]

[0009] Aspect 1 of the present invention is C: 0.30~0.45% by mass, Si:0.10~0.40% by mass, Mn: 0.50~1.00% by mass, P: 0.050% by mass or less, S: 0.050% by mass or less, Cr:0.80~1.30% by mass, Al: 0.01~0.10% by mass, The balance is composed of iron and inevitable impurities. The area ratio of pro-eutectoid ferrite is 10% or more and 70% or less, and the steel includes one or more selected from the group consisting of bainite, martensite, and pearlite, Dislocation density is 3.5×10 14 m -2 That's all. It is a mechanical structural steel for cold working.

[0010] A second aspect of the present invention is the steel for machine structural use for cold working according to the first aspect, wherein the pro-eutectoid ferrite has an average crystal grain size of 6 μm or less.

[0011] Aspect 3 of the present invention is Cu: 0.25 mass% or less (excluding 0 mass%) Ni: 0.25 mass% or less (excluding 0 mass%), and The steel for machine structural use for cold working according to embodiment 1 or 2, further containing one or more selected from the group consisting of: Mo: 0.40 mass % or less (not including 0 mass %).

[0012] A fourth aspect of the present invention is Ti: 0.20 mass% or less (excluding 0 mass%) Nb: 0.20 mass% or less (excluding 0 mass%), and V: 1.50 mass % or less (excluding 0 mass %) of one or more selected from the group consisting of:

[0013] A fifth aspect of the present invention is N: 0.01% by mass or less (excluding 0% by mass), Mg: 0.02% by mass or less (excluding 0% by mass), Ca: 0.05% by mass or less (excluding 0% by mass), Li: 0.02% by mass or less (excluding 0% by mass), and The steel for machine structural use for cold working according to any one of Aspects 1 to 4, further comprising one or more selected from the group consisting of REM: 0.05 mass % or less (excluding 0 mass %).

[0014] A sixth aspect of the present invention is (a) hot working at a working temperature T0 between 800°C and 1000°C with a compression ratio of 20% or more; (b) after the step (a), cooling to a first cooling temperature T1 of 670°C or more and 730°C or less at a first cooling rate CR1 of 5°C / sec or more; (c) after the step (b), maintaining the first cooling temperature T1 for a retention time t1 of 10 to 600 seconds; (d) after the step (c), cooling to a second cooling temperature T2 of 550° C. or lower at a second cooling rate CR2 of 5° C. / sec or higher.

[0015] A seventh aspect of the present invention is a method for producing a steel wire, in which a steel for cold working mechanical structural use produced by the method described in the sixth aspect is subjected to one or more processes of annealing, spheroidizing annealing, wire drawing, heading, and quenching and tempering. Effect of the Invention

[0016] In one embodiment of the present invention, it is possible to provide a steel for machine structural use for cold working that can be sufficiently softened even at a relatively low spheroidizing annealing temperature and for a spheroidizing annealing time that is clearly shorter than in the past, and to provide a method for producing the same. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic diagram showing a thermomechanical treatment pattern (thermomechanical treatment history) of a steel material in a manufacturing method of structural steel for cold working according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing the spheroidizing annealing conditions (SA1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The inventors have conducted research from various angles, and have discovered that a steel for machine structural use for cold working having a prescribed composition contains an appropriate amount of pro-eutectoid ferrite, in terms of area ratio, of 10% or more and 70% or less, the portion of the metal structure other than the pro-eutectoid ferrite contains one or more selected from the group consisting of bainite, martensite, and pearlite, and the dislocation density is 3.5×10 14 m -2It has been found that by doing as described above, it is possible to realize a steel for machine structural use for cold working that can be sufficiently softened even when the temperature in spheroidizing annealing is relatively low and the time is obviously short.

[0019] The inventors have also found that such a steel for mechanical structural use for cold working can be manufactured by: (a) hot working a steel having a predetermined composition at a working temperature T0 exceeding 800°C and not exceeding 1000°C with a compression ratio of 20% or more; (b) after step (a), cooling to a first cooling temperature T1 of 670°C or more and 730°C or less at a first cooling rate CR1 of 5°C / sec or more; (c) after step (b), holding at the first cooling temperature T1 for a holding time t1 of 10 to 600 seconds; and (d) after step (c), cooling to a second cooling temperature T2 of 550°C or less at a second cooling rate CR2 of 5°C / sec or more.

[0020] The details of the embodiment of the present invention are given below. In this specification, the term "wire rod" refers to a rolled wire rod and indicates a linear steel material that has been subjected to hot rolling and a subsequent cooling step to room temperature. Also, the term "steel wire" refers to a linear steel material whose properties have been adjusted by subjecting the rolled wire rod to annealing or the like.

[0021] <1.Chemical composition> The steel for machine structural use for cold work according to an embodiment of the present invention contains C: 0.30 to 0.45 mass%, Si: 0.10 to 0.40 mass%, Mn: 0.50 to 1.00 mass%, P: 0.050% or less, S: 0.050% or less, Cr: 0.80 to 1.30 mass%, and Al: 0.01 to 0.10 mass%. Each element will be described in detail below.

[0022] (C:0.30~0.45% by mass) C is a strength-imparting element, and if it is less than 0.30 mass%, the necessary strength of the final product cannot be obtained. On the other hand, if it exceeds 0.45 mass%, the cold workability and toughness of the steel decrease. Therefore, the C content is set to 0.30 to 0.45 mass%. In addition, the C content is preferably 0.43 mass% or less, and more preferably 0.40 mass% or less. This is because it allows more pro-eutectoid ferrite to precipitate.

[0023] (Si:0.10~0.40% by mass) Silicon is useful as a deoxidizing element and as a strength-improving element that is added for the purpose of increasing the strength of the final product by solid solution hardening. To effectively exert such effects, the Si content is set to 0.10 mass% or more. On the other hand, if Si is contained in excess, the hardness increases excessively and the cold workability of the steel deteriorates. Therefore, the Si content is set to 0.40 mass% or less.

[0024] (Mn:0.50~1.00% by mass) Mn is an effective element for increasing the strength of the final product by improving the hardenability. To effectively exert this effect, the Mn content is set to 0.50 mass% or more. On the other hand, if Mn is contained in excess, the hardness increases and the cold workability of the steel deteriorates. Therefore, the Mn content is set to 1.00 mass% or less.

[0025] (P: 0.050 mass% or less) P is an element that is inevitably contained in steel and causes grain boundary segregation in steel, which leads to deterioration of the ductility of the steel, so the P content is set to 0.050 mass% or less.

[0026] (S: 0.050% by mass or less) S is an element that is inevitably contained in steel, and exists in the steel as MnS, which deteriorates the ductility of the steel, and is therefore a harmful element that deteriorates the cold workability of the steel. Therefore, the S content is set to 0.050 mass% or less.

[0027] (Cr: 0.80 mass% or more and 1.30 mass% or less) Cr is an effective element for increasing the strength of the final product by improving the hardenability of the steel material. To effectively exert this effect, the Cr content is set to 0.80 mass% or more. This effect increases as the Cr content increases. However, if the Cr content is excessive, the strength becomes too high and the cold workability of the steel deteriorates, so the Cr content is set to 1.30 mass% or less.

[0028] (Al: 0.01 mass% or more and 0.10 mass% or less) Al is useful as a deoxidizer and also combines with N to precipitate AlN, preventing the abnormal growth of crystal grains during processing and the resulting decrease in strength. In order to effectively exert this effect, the Al content is set to 0.01 mass% or more, preferably 0.015 mass% or more, and more preferably 0.020 mass% or more. However, if the Al content is excessive, Al2O3 is generated in excess, deteriorating cold forgeability. Therefore, the Al content is set to 0.10 mass% or less, preferably 0.090 mass% or less, and more preferably 0.080 mass% or less.

[0029] The basic components are as described above, and in one preferred embodiment, the balance is iron and inevitable impurities. As inevitable impurities, elements (e.g., B, As, Sn, Sb, Ca, O, H, etc.) that are brought in due to the circumstances of raw materials, materials, manufacturing facilities, etc. are allowed to be mixed in. In addition, for example, P and S, which are usually preferable as their content is small, are unavoidable impurities, but their composition ranges are separately specified as above. Therefore, in this specification, when referring to "unavoidable impurities" that make up the balance, this concept excludes elements whose composition ranges are separately specified.

[0030] (Other optional elements) In addition, in another preferred embodiment of the present invention, elements other than those described above may be added as necessary within a range that does not impair the effects according to the embodiment of the present invention. Examples of such selected elements are shown below. The properties of the steel are further improved depending on the components contained. In addition, the description of "not containing 0 mass %" for other optional elements means that the element is intentionally added, except for the amount that is unavoidably contained as an impurity (impurity level amount).

[0031] (One or more selected from the group consisting of Cu: 0.25 mass% or less (excluding 0 mass%), Ni: 0.25 mass% or less (excluding 0 mass%), and Mo: 0.40 mass% or less (excluding 0 mass%)) Cu: 0.25 mass% or less (excluding 0 mass%), Ni: 0.25 mass% or less (excluding 0 mass%) Cu and Ni are elements that improve hardenability and effectively act to increase product strength. Such effects increase as the contents of these elements increase, but to effectively exert these effects, Cu and Ni are preferably 0.05 mass% or more, more preferably 0.08 mass% or more, and even more preferably 0.10 mass% or more, respectively. However, if they are contained in excess, excessive supercooled structures are formed, and the strength becomes too high, resulting in a decrease in cold forgeability. Therefore, Cu and Ni are preferably 0.25 mass% or less, respectively. More preferably, they are 0.22 mass% or less, and even more preferably, they are 0.20 mass% or less. Cu and Ni may be contained alone, or both may be contained. When both Cu and Ni are contained, the contents may be any contents within the above ranges.

[0032] Mo: 0.40% by mass or less (excluding 0% by mass) Mo is an effective element for increasing the strength of the final product by improving the hardenability of the steel material, and therefore may be intentionally added. Such an effect becomes greater as the Mo content increases. However, if the Mo content becomes excessive, the strength becomes too high and the cold workability of the steel deteriorates. In particular, when Mo is contained in steel together with Cr, the steel may become significantly less likely to soften after spheroidizing annealing. Therefore, Mo is set to 0.40 mass% or less.

[0033] (One or more selected from the group consisting of Ti: 0.20 mass% or less (excluding 0 mass%), Nb: 0.20 mass% or less (excluding 0 mass%), and V: 1.50 mass% or less (excluding 0 mass%)) Ti, Nb, and V are elements that combine with N to form compounds (nitrides), reduce the amount of dissolved N in the steel, and obtain the effect of reducing deformation resistance. In order to exert such an effect, Ti, Nb, and V are each preferably contained in an amount of 0.05 mass% or more, more preferably 0.06 mass% or more, and even more preferably 0.08 mass% or more. However, if these elements are contained in excess, the amount of nitrides increases, the deformation resistance increases, and the cold forgeability deteriorates, so Ti and Nb are each preferably 0.20 mass% or less, more preferably 0.18 mass% or less, and even more preferably 0.15 mass% or less, and V is preferably 1.50 mass% or less, more preferably 1.30 mass% or less, and even more preferably 1.00 mass% or less. Ti, Nb, and V may each be contained alone or in combination of two or more kinds, and when two or more kinds are contained, the content may be any content within the above range.

[0034] (One or more selected from the group consisting of N: 0.01% by mass or less (not including 0% by mass), Mg: 0.02% by mass or less (not including 0% by mass), Ca: 0.05% by mass or less (not including 0% by mass), Li: 0.02% by mass (not including 0% by mass), and rare earth elements (Rare Earth Metals: REM): 0.05% by mass or less (not including 0% by mass)) N is an impurity that is inevitably contained in steel, but if solid solution N is contained in steel, it causes an increase in hardness and a decrease in ductility due to strain aging, and the cold forgeability is deteriorated. Therefore, the N content is preferably 0.01 mass% or less, more preferably 0.009 mass% or less, and even more preferably 0.008 mass% or less. In addition, Mg, Ca, Li, and REM are elements that are effective in spheroidizing sulfide compound inclusions such as MnS and improving the deformability of steel. Although such effects increase as the content increases, in order to effectively exert them, the contents of Mg, Ca, Li, and REM are preferably 0.0001 mass% or more, more preferably 0.0005 mass% or more, respectively. However, even if they are contained excessively, the effect is saturated and an effect commensurate with the content cannot be expected, so the contents of Mg and Li are preferably 0.02 mass% or less, more preferably 0.018 mass% or less, and even more preferably 0.015 mass% or less, respectively. The Ca and REM contents are each preferably 0.05% by mass or less, more preferably 0.045% by mass or less, and even more preferably 0.040% by mass or less. Each of N, Ca, Mg, Li, and REM may be contained alone or in combination of two or more kinds, and when two or more kinds are contained, the content may be any content within the above range. The REM content refers to the total content of 17 elements, including the two elements Sc and Y and the 15 elements from La to Lu, and containing REM means containing one or more elements selected from these 17 elements.

[0035] <2.Metal structure> The steel for cold working machine structural use according to the embodiment of the present invention contains pro-eutectoid ferrite in an area ratio of 10% or more and 70% or less. Pro-eutectoid ferrite contributes to softening of the steel after spheroidizing annealing. However, the mere inclusion of pro-eutectoid ferrite does not realize a steel that can be sufficiently softened after spheroidizing annealing at a relatively low temperature for a short time. Therefore, the inventors of the present application have discovered that by increasing the dislocation density, it is possible to suppress hardness and hardness variations, and to sufficiently soften the steel, even when spheroidizing annealing is performed at a relatively low temperature for a short time.

[0036] Specifically, the portion other than the proeutectoid ferrite (the remaining metal structure) contains one or more selected from the group consisting of bainite, martensite, and pearlite. As described in detail below, the dislocation density within bainite, martensite, and pearlite can be increased by performing an appropriate thermomechanical treatment. As a result, the dislocation density as a whole (i.e., as the overall average of all the metal structures) can be increased to 3.5×10 14 m -2 It can do more than that.

[0037] [2-1. Area ratio of pro-eutectoid ferrite: 10% to 70%] By allowing a large amount of pro-eutectoid ferrite to exist, it is possible to promote the aggregation and spheroidization of carbides such as cementite during spheroidizing annealing, and as a result, the hardness of the steel can be reduced. From this viewpoint, the area ratio of pro-eutectoid ferrite needs to be 10% or more. The area ratio of pro-eutectoid ferrite is preferably 20% or more, more preferably 30% or more, and even more preferably 40% or more. On the other hand, in order to obtain pro-eutectoid ferrite with an area ratio exceeding 70%, special treatment such as slow cooling and holding for a very long time is required, so that it is difficult to use general mass production equipment. For this reason, the upper limit of the area ratio of pro-eutectoid ferrite is set to 70%.

[0038] The area ratio of a specific metal structure such as pro-eutectoid ferrite can be determined by drawing lines in a grid pattern on a metal structure photograph, counting the number of intersections (grid points) where the structure exists, and calculating the ratio of the counted value to the total number of intersections. In this case, if an intersection is on the boundary between the target metal structure such as pro-eutectoid ferrite and another metal structure, it is counted as 0.5 points. The position for observing the metal structure is the midpoint between the center and the surface, that is, in the case of a wire, the position is one-quarter of the wire diameter D from the surface (D / 4 position).

[0039] [2-2. One or more selected from the group consisting of bainite, martensite, and pearlite] In addition to the above pro-eutectoid ferrite, the alloy contains one or more selected from the group consisting of bainite, martensite and pearlite. By applying appropriate thermomechanical treatment to bainite, martensite, and pearlite, as described below, it is possible to increase the density of dislocations formed inside the transformation. The formation of a metal structure with such a high dislocation density results in an overall 14 m -2 A high dislocation density can be obtained.

[0040] Any one of bainite, martensite and pearlite may be present, or two or more of them may be present. In addition, the amount (area ratio) of bainite, martensite, and pearlite was 3.5 × 10 14 m -2 Any value may be used as long as the dislocation density is equal to or greater than the above value. The total of bainite, martensite, and pearlite (the total of bainite, martensite, and pearlite that are present) is preferably 50% or more, and more preferably 70% or more, in terms of area ratio, relative to the entire metal structure other than the above-mentioned pro-eutectoid ferrite (the remaining metal structure). It is even more preferable that the entire remaining metal structure is composed of one or more of bainite, martensite, and pearlite, because the desired dislocation density can be obtained more easily. Note that "the entire remaining metal structure is composed of one or more of bainite, martensite, and pearlite" may include a case where, as a result of observing a relatively narrow field of view, no metal structure other than bainite, martensite, and pearlite is observed in the remaining metal structure, but a small amount of metal structure other than bainite, martensite, and pearlite is observed by observing a wider field of view.

[0041] In addition, the term "pearlite" used in this specification is a concept including not only a form in which the so-called lamellar structure can be clearly observed, but also so-called "fine pearlite" in which the cementite is divided and does not have a neat lamellar structure. The pearlite is preferably made of fine pearlite, since this makes it easier to obtain the desired dislocation density.

[0042] [2-3. Dislocation density is 3.5×10 14 m -2 End] The steel for cold working machine structural use according to the embodiment of the present invention has a dislocation density of 3.5×10 14 m -2 or more, preferably 5×10 14 m -2 That is all. By making the dislocation density high, it is possible to promote the decomposition and solid solution of carbides during spheroidizing annealing. As a result, even when spheroidizing annealing is performed at a relatively low temperature for a short time, it is possible to suppress the variation in hardness and achieve sufficient softening. The dislocation density is preferably less than 1×10 16 m -2 The dislocation density is 1×10 16 m -2 If the temperature exceeds this range, depending on the heat treatment conditions in the spheroidizing annealing, the dislocation density after the spheroidizing annealing may become relatively high, and the hardness may become high.

[0043] Such a high dislocation density cannot be achieved simply by the presence of one or more of bainite, martensite, and pearlite, but can be achieved by increasing the number of dislocations introduced with the transformation through appropriate thermomechanical treatment, as described below.

[0044] The dislocation density can be determined from the strain (lattice strain) and Burgers vector values ​​obtained by the Williamson-Hall (WH) method in X-ray diffraction, as will be described in detail in the Examples.

[0045] [2-4. Average grain size of proeutectoid ferrite is 6μm or less] In the steel for cold working machine structural use according to the embodiment of the present invention, the average crystal grain size of the pro-eutectoid ferrite is preferably 6 μm or less. By making the average crystal grain size of the pro-eutectoid ferrite 6 μm or less, the hardness variation after spheroidizing annealing can be more reliably suppressed.

[0046] <3. Manufacturing method> The steel for cold working machine structural use according to the embodiment of the present invention can be produced by performing a predetermined hot working in a predetermined temperature range, followed by a thermo-mechanical treatment involving cooling and holding under predetermined conditions, as will be described in detail below. Fig. 1 is a schematic diagram showing a thermomechanical treatment pattern (thermomechanical treatment history) of a steel material in a manufacturing method of structural steel for cold working according to the present invention. In the manufacturing method shown in Fig. 1, a steel material such as a wire rod having the above-mentioned chemical composition is subjected to a thermomechanical treatment including the following steps (a) to (d). (a) A process of performing hot working at a working temperature T0 exceeding 800°C and not exceeding 1000°C with a compression ratio of 20% or more. (b) after step (a), a step of cooling to a first cooling temperature T1 of 670°C or more and 730°C or less at a first cooling rate CR1 of 5°C / s or more; (c) after step (b), a step of holding the first cooling temperature T1 for a holding time t1 of 10 to 600 seconds; (d) after step (c), cooling to a second cooling temperature T2 of 550° C. or less at a second cooling rate CR2 of 5° C. / s or more; Each step is described below.

[0047] [Step (a): A step of performing hot working at a working temperature T0 of more than 800°C and less than 1000°C with a compression ratio of 20% or more] As shown in Figure 1, a steel material (e.g., wire rod) having the above-mentioned chemical composition is heated to a temperature T0 (working temperature T0) and hot worked. The working temperature T0 is higher than 800°C and not higher than 1000°C. The compression ratio of the hot working is 20% or more. In order to secure the necessary amount of pro-eutectoid ferrite, the working temperature T0 is set to 1000°C or less and the compression ratio of the hot working is set to 20% or more. In addition, by setting the working temperature T0 to 1000°C or less and the compression ratio of the hot working is set to 20% or more, it is possible to have the effect of making the pro-eutectoid ferrite grains fine. When the processing temperature T0 is 800°C or lower, the transformation in the high temperature region is promoted during the subsequent cooling, and the dislocation density is reduced to 3.5×10 14 m -2 Therefore, the processing temperature T0 is set to more than 800°C.

[0048] The hot working may be in any form as long as it can achieve a compression ratio of 20% or more. Examples of hot working include pressing and rolling. The compression ratio is calculated as follows: <Compression ratio when performing press working (in this case, compression ratio is also called rolling reduction)> Compression ratio (%) = (h1-h2) / h1 x 100 h1: Height of steel before processing, h2: Height of steel after processing <Compression ratio when obtaining wire rod by rolling (in this case, the compression ratio is also called the area reduction ratio)> Compression ratio (%) = (S1-S2) / S1 x 100 S1: Cross-sectional area of ​​steel before processing, h2: Cross-sectional area of ​​steel after processing The compression ratio may be 20% or more in one hot working, or the total compression ratio may be 20% or more by performing hot working multiple times while maintaining the temperature at T0.

[0049] [Step (b): After step (a), a step of cooling to a first cooling temperature T1 of 670° C. or more and 730° C. or less at a first cooling rate CR1 of 5° C. / sec or more] After step (a), as shown in FIG. 1, the steel is cooled to a first cooling temperature T1 at a first cooling rate CR1. The first cooling temperature T1 is 670° C. or more and 730° C. or less. The first cooling rate CR1 is 5° C. / sec or more. By cooling to the first cooling temperature T1 at 5° C. / sec or more, the dislocation density of the obtained structural steel for cold working is reduced to 3.5×10 14 m -2 Moreover, by setting the first cooling rate CR1 to 5° C. / sec or more, the pro-eutectoid ferrite grains can be made fine. The cooling rate may be measured by bringing a contact thermometer such as a thermocouple into contact with the steel material, or, as a simple method, by measuring the surface temperature of the steel material using a non-contact thermometer.

[0050] [Step (c): After step (b), a step of maintaining the first cooling temperature T1 for a retention time t1 of 10 to 600 seconds] After the step (b), as shown in FIG. 1, the material is held at a first cooling temperature T1 for a holding time t1. The holding time t1 is 10 to 600 seconds, preferably 10 to 400 seconds, and more preferably 10 to 200 seconds. In order to obtain a pro-eutectoid ferrite amount of 10 to 70% in terms of area ratio, the holding time t1 at the first cooling temperature T1 is set to 10 seconds or more. On the other hand, if the holding time t1 exceeds 600 seconds, the density of dislocations generated in association with the phase transformation occurring during further cooling from the first cooling temperature T1 will be 3.5×10 14 m -2 If the holding time t1 is too long, C and other alloy elements will become concentrated in the austenite, and the growth of ferrite that occurs in the subsequent cooling process will be suppressed, making it difficult to ensure a sufficient ferrite area ratio, so the holding time t1 is set to 600 seconds or less. The holding time t1 is preferably 400 seconds or less, and more preferably 200 seconds or less.

[0051] [Step (d): After step (c), a step of cooling to a second cooling temperature T2 of 550° C. or less at a second cooling rate CR2 of 5° C. / sec or more] After the step (c), as shown in FIG. 1, the steel is cooled to a second cooling temperature T2 at a second cooling rate CR2. The second cooling temperature T2 is 550° C. or less. The second cooling rate CR2 is 5° C. / sec or more. The second cooling rate CR2 is preferably 50° C. / sec or less. The dislocation density of the obtained structural steel for cold working is 3.5×10 14 m -2 To achieve the above temperature, cooling is performed at a cooling rate of 5° C. / sec or more between the first cooling temperature T1 and a temperature T2 of 550° C. or less.

[0052] Regarding cooling to a temperature lower than the second cooling temperature T2 after step (d), the embodiment shown in FIG. 1 illustrates, by way of example, holding at the second cooling temperature T2 for a holding time t2, and then cooling to room temperature at a third cooling rate CR3 (e.g., furnace cooling, natural cooling or rapid cooling (e.g., gas rapid cooling)). However, the present invention is not limited to this, and any cooling method may be used. As an example of such cooling, the second cooling temperature T2 may be room temperature, and the material may be cooled from the first cooling temperature T1 to room temperature at a second cooling rate CR2. When the second cooling temperature T2 is held for the holding time t2, it is preferable that the second cooling temperature T2 is 400°C to 550°C and the holding time t2 is 100 to 3000 seconds. By setting the second cooling temperature T2 to 400°C or more, a desired ferrite area ratio can be obtained more easily. The second cooling temperature T2 is more preferably 500°C or more. By setting the second cooling temperature T2 to 550°C or less, a high dislocation density can be obtained more easily. The second cooling temperature T2 is more preferably 540°C or less. By setting the holding time t2 to 100 seconds or more, a desired ferrite area ratio can be obtained more easily. The holding time t2 is more preferably 150 seconds or more, and further preferably 210 seconds or more. By setting the holding time t2 to 3000 seconds or less, a high dislocation density can be obtained more easily while ensuring high productivity. The holding time t2 is more preferably 1500 seconds or less. In addition, after cooling to the second cooling temperature T2 and the second cooling rate CR2, the material may be cooled from the second cooling temperature T2 to room temperature at a third cooling rate CR3 different from the second cooling rate CR2 without holding (i.e., holding time t2 is 0 seconds). In this case, the third cooling rate CR3 may be faster or slower than the second cooling rate CR2. Examples of the cooling method for obtaining the third cooling rate CR3 include furnace cooling, natural cooling, and quenching (e.g., gas quenching). In this case, the second cooling rate CR2 and the third cooling rate CR3 are preferably 1 to 25°C / sec. If the second cooling rate CR2 and the third cooling rate CR3 are 1°C / sec or more, a high dislocation density can be obtained more easily, and if the second cooling rate CR2 and the third cooling rate CR3 are 25°C / sec or less, a desired ferrite area ratio can be obtained more easily.

[0053] The manufacturing method described above makes it possible to obtain the steel for cold working machine structural use according to the embodiment of the present invention. The steel for cold working for mechanical structural use according to the embodiment of the present invention is assumed to be subsequently subjected to spheroidizing annealing, but in some cases, other processing (wire drawing, etc.) may be performed before or after spheroidizing annealing. The steel for cold working machine structure according to the embodiment of the present invention can be sufficiently softened even at a relatively low temperature of 750°C, for example, as shown in the examples described below, by shortening the spheroidizing annealing time (the total of the holding time at a predetermined holding temperature and the cooling time from the holding temperature to a predetermined air-cooling start temperature) to about 5 hours or less, which is significantly shorter than the conventional time (about 11 hours in Patent Document 1). In addition, in the present invention, a steel wire can be manufactured by subjecting the steel material (structural steel for cold working) obtained under the above manufacturing conditions to one or more processes of annealing, spheroidizing annealing, wire drawing, heading, and quenching and tempering. The steel wire referred to here refers to a wire-shaped steel material obtained under the above manufacturing conditions and has its properties adjusted by subjecting the steel material obtained under the above manufacturing conditions to annealing, spheroidizing annealing, wire drawing, heading, quenching and tempering, etc., but also includes a wire-shaped steel material that has undergone a process generally performed by a secondary processing manufacturer in addition to the above annealing process.

[0054] As described above, the manufacturing method for steel for cold working machine structural use according to the embodiment of the present invention has been described. However, a person skilled in the art who understands the desired properties of the steel for cold working machine structural use according to the embodiment of the present invention may find, through trial and error, a method for manufacturing steel for cold working machine structural use having the desired properties according to the embodiment of the present invention, other than the manufacturing method described above. EXAMPLES

[0055] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the above and below-mentioned aims, and all such modifications are included in the technical scope of the present invention. [Table 1]

[0056] Test pieces for processing formasters measuring φ8 mm × 12 mm were prepared using rolled materials of steel type 1 (SCM435), steel type 2 (SCM440), and steel type 3 (SCR440) listed in Table 1. SCM435, SCM440, and SCR440 are steel types specified in the Japanese Industrial Standard JIS G 4053. As shown in Table 1, steel type 1 and steel type 2 contain Cu and Ni, but both are at the impurity level, i.e., Cu and Ni are unavoidable impurities and not intentionally added. Steel type 3 contains 0.01 mass% Mo, but at the impurity level, i.e., the Mo in steel type 3 is an unavoidable impurity and not intentionally added.

[0057] The test pieces for the processing Formaster thus prepared were subjected to the thermomechanical treatment shown in FIG. 1 using a Processing Formaster testing machine to prepare samples of structural steel for cold working. The specimen was heated at a rate of 10°C / s up to the processing temperature T0, and after reaching the processing temperature T0, it was held for 300 seconds, after which it was pressed twice as hot processing. In the first press, the height of the specimen was reduced from 12 mm to 7 mm (ε = 0.54) at a strain rate of 50 / s, and 5 seconds later, the second press was performed at a strain rate of 50 / s, reducing the height of the specimen from 7 mm to 3 mm (ε = 0.85).

[0058] The processing temperature T0, the first cooling temperature T1, the first cooling rate CR1, the holding time t1, the second cooling temperature T2, and the second cooling rate CR2 are shown in Table 2. For reference, the holding time t2 and the third cooling rate CR3 are also shown in Table 2. Samples No. 1-3 and No. 1-4 are samples in which the second cooling temperature T2 is room temperature, and therefore the samples are cooled from the first cooling temperature T1 to room temperature at the second cooling rate CR2. Samples No. 1-5, No. 2-2 and No. 3-4 are samples in which the samples were hot worked at the working temperature T0 and then cooled to room temperature at 30°C / s. Incidentally, any deviation from the conditions shown in the manufacturing method of the embodiment of the present invention described above is underlined.

[0059] [Table 2]

[0060] The sample after the thermomechanical treatment was cut along the central axis and divided into four equal parts, to obtain four samples including the longitudinal section. One of the samples was not subjected to spheroidizing annealing (hereinafter, may be referred to as the sample before spheroidizing annealing), and the other was subjected to spheroidizing annealing (hereinafter, may be referred to as the sample after spheroidizing annealing). The spheroidizing annealing was performed by placing each sample in a vacuum sealed tube.

[0061] FIG. 2 is a schematic diagram showing the spheroidizing annealing conditions (SA1). The spheroidizing annealing was performed by heating to 750°C at a rate of 80°C / hour, holding for 1 hour, and then cooling to 660°C at a rate of 30°C / hour, and then allowing to cool. That is, the spheroidizing annealing temperature is relatively low at 750°C, the spheroidizing annealing time is remarkably short at about 4.7 hours, and the holding time is also remarkably short at 1 hour.

[0062] The samples before spheroidizing annealing were embedded in resin so that the longitudinal cross section could be observed, and (1) the area ratio of pro-eutectoid ferrite and structures other than pro-eutectoid ferrite were measured, (2) the average crystal grain size of pro-eutectoid ferrite was measured, and (3) the dislocation density was measured. In addition, the samples after spheroidizing annealing were also embedded in resin so that the longitudinal cross section could be observed in the same manner as above, and (4) the hardness and its variation after spheroidizing annealing were measured. In all of the measurements and observations (1) to (4), the diameter of the sample was defined as D, and the measurements and observations were performed at a position of D / 4 from the surface of the sample toward the central axis.

[0063] (1) Measurement of the area ratio of proeutectoid ferrite The longitudinal section of the sample before spheroidizing annealing was subjected to nital etching to reveal the structure, and a photograph was taken at the D / 4 position with an optical microscope at a magnification of 400x (field of view: 220 μm horizontal × 165 μm vertical). On the obtained photograph, 15 equally spaced vertical lines and 10 equally spaced horizontal lines were drawn in a grid pattern, the number of pro-eutectoid ferrite points present at the 150 intersections was counted, and the value obtained by dividing the number of lines by 150 was determined as the area ratio (%) of pro-eutectoid ferrite. In this case, if the lattice was at the boundary between pro-eutectoid ferrite and other structures, it was set to 0.5. Additionally, for the portion other than the pro-eutectoid ferrite (the remaining metal structure), the phase was identified by metal structure observation.

[0064] (2) Measurement of the average grain size of proeutectoid ferrite The longitudinal section of the sample before spheroidizing annealing was subjected to nital etching to reveal the structure, and photographs were taken at the D / 4 position using an optical microscope at a magnification of 400x (field of view: 220μm horizontal × 165μm vertical) or 1000x (field of view: 147μm horizontal × 110μm vertical).The size (equivalent circle diameter) of each pro-eutectoid ferrite grain in the field of view was calculated using image analysis software (Image-Pro Plus ver7.0), and the average value was taken as the average crystal grain size of the pro-eutectoid ferrite. Note that pro-eutectoid ferrite grains in contact with the edge of the photograph (pro-eutectoid ferrite grains whose actual grain size cannot be measured) were excluded from the count.

[0065] (3) Measurement of dislocation density The samples before spheroidizing annealing were electrolytically polished to prepare samples for measuring dislocation density, which were then subjected to X-ray diffraction analysis using a horizontal X-ray diffractometer, SmartLab, manufactured by Rigaku Corporation. The X-ray diffraction profile was measured using Co as the target metal by the θ / 2θ diffraction method in the 2θ range of 40° to 130°.

[0066] The obtained diffraction profile was used to calculate the strain by the Williamson-Hall (WH) method, using the following equation: βcosθ / λ=0.9 / D+2εsinθ / λ (Equation 1) β 2 =β m 2 -β s 2 (Formula 2) Here, β is the true half-width (rad), θ is the Bragg angle (rad), λ is the incident X-ray wavelength (nm) (λ was 0.1789 nm), D is the crystallite size (nm), and ε is the lattice distortion. The broadening of the diffraction line width due to the instrument constant was corrected using the approximate formula (Equation 2). m is the measured half-width, β s is the half-width (instrumental function) for the unstrained sample. The unstrained sample used was Si640d manufactured by NIST.

[0067] More specifically, the diffraction peaks of the (110), (211), and (220) planes of the proeutectoid ferrite (α-Fe) of the sample were measured, and the diffraction angle 2θ and the half-width β m asked for. The horizontal axis represents sin θ / λ and the vertical axis represents βcos θ / λ, and the measurement results of each of the above crystal planes are plotted. An approximation curve was drawn using a linear function (y = ax + b) for the plot. The strain (ε) and crystallite size (D) can be calculated from the slope and intercept of the straight line, so the strain (ε) was calculated from this.

[0068] The dislocation density ρ can be expressed as (Equation 3) using the strain ε and the Burgers vector b. ρ=14.4ε 2 / b 2 (Formula 3) Here, the magnitude of the Burgers vector b is 0.25×10 -9 m was used. From this, the dislocation density ρ was calculated.

[0069] (4) Hardness and its variation after spheroidizing annealing In order to confirm the effect of softening by spheroidizing annealing, the hardness of the longitudinal section of the sample after spheroidizing annealing was measured at five locations (five points) at the D / 4 position using a Vickers hardness tester with a load of 1 kgf. The average value (HV) was taken as the hardness (HV) of the sample, and the standard deviation was calculated from the measured values ​​and taken as the hardness variation (HV). For samples related to steel type 1 (SCM435), if the hardness was HV 165 or less and the hardness variation was HV 7.0 or less, it was judged that the sample was sufficiently softened. On the other hand, for samples related to steel type 2 (SCM440) and steel type 3 (SCR440), which have a higher C content, if the hardness was HV 180 or less and the hardness variation was HV 7.0 or less, it was judged that the sample was sufficiently softened.

[0070] Table 3 shows the area ratio of pro-eutectoid ferrite, the structure other than pro-eutectoid ferrite, the average crystal grain size of pro-eutectoid ferrite, the dislocation density, the hardness after spheroidizing annealing, and the variation in the hardness, all of which were determined by the methods described above. In Table 3, cases that deviate from the requirements shown in the embodiments of the present invention and cases that deviate from the criteria for softening evaluation are underlined. Furthermore, with regard to structures other than pro-eutectoid ferrite, the term "mainly" means that no other type of metal structure was observed within the above-mentioned observation field (220 μm wide × 165 μm long) (however, this does not negate the possibility that small amounts of other metal structures may be observed when a wider field is observed). In addition, pearlite observed in the structure other than the pro-eutectoid ferrite of sample No. 2-1 was fine pearlite.

[0071] [Table 3]

[0072] From Tables 2 and 3, the following can be concluded: Samples No. 1-1, 1-2, 1-3, 2-1 and 3-1 to 3-3 are examples that satisfy all of the requirements defined in the embodiments of the present invention. After spheroidizing annealing at a relatively low temperature of 750°C for a fairly short time (holding time of 1 hour, spheroidizing annealing time of about 4.7 hours), both hardness and hardness variation were good, that is, the samples were sufficiently softened. On the other hand, Samples Nos. 1-4, 1-5, 1-6, 2-2 and 3-4 are examples that do not satisfy one or more of the requirements defined in the present invention, and at least one of the hardness and hardness variation after spheroidizing annealing was poor, that is, the softening was insufficient.

[0073] In sample No. 1-4, the processing temperature T0 was too high, the first cooling temperature T1 was too low, and the holding time t1 was too long. This resulted in an excessively low dislocation density. As a result, the hardness and hardness variation after spheroidizing annealing were poor.

[0074] In sample No. 1-5, the first cooling temperature T1 was room temperature, which was too low, and therefore the holding time t1 at the appropriate first cooling temperature T1 (670°C to 730°C) could not be secured. As a result, sufficient pro-eutectoid ferrite could not be obtained, and the hardness after spheroidizing annealing was poor.

[0075] In sample No. 1-6, the processing temperature T0 was too high, the first cooling temperature T1 was too high, and the second cooling rate CR2 was too slow. This resulted in an excessively low dislocation density. The amount of pro-eutectoid ferrite was sufficient, so the hardness value after spheroidizing annealing was good, but the hardness variation was poor due to the low dislocation density.

[0076] In sample No. 2-2, the first cooling temperature T1 was too low, i.e., room temperature, and therefore the holding time t1 at the appropriate first cooling temperature T1 (670°C to 730°C) could not be secured. As a result, sufficient pro-eutectoid ferrite could not be obtained, and the hardness after spheroidizing annealing was poor.

[0077] In sample No. 3-4, the first cooling temperature T1 was room temperature, which was too low, and therefore the holding time t1 at the appropriate first cooling temperature T1 (670°C to 730°C) could not be secured. As a result, sufficient pro-eutectoid ferrite could not be obtained, and the hardness after spheroidizing annealing was poor.

[0078] The steel for cold working machine structure according to the present invention is suitable as a material for various parts manufactured by cold working such as cold forging, cold heading, cold rolling, etc. The form of the steel is not particularly limited, but it can be, for example, a rolled material such as a wire rod or a bar steel. The parts include, for example, automobile parts and construction machine parts, and specifically include bolts, screws, nuts, sockets, ball joints, inner tubes, torsion bars, clutch cases, cages, housings, hubs, covers, cases, catch washers, tappets, saddles, bulges, inner cases, clutches, sleeves, outer races, sprockets, stators, anvils, spiders, rocker arms, bodies, flanges, drums, joints, connectors, pulleys, metal fittings, yokes, ferrules, valve lifters, spark plugs, pinion gears, steering shafts, and common rails. The steel for cold working machine structural use according to the present invention is industrially useful as a machine structural use steel that is suitably used as a material for the above-mentioned parts, and can exhibit low deformation resistance and excellent cold workability when manufactured into the above-mentioned various parts at room temperature and in the region of heat generation due to processing after spheroidizing annealing.

Claims

1. C: 0.30 to 0.45% by mass, Si: 0.10 to 0.40% by mass, Mn: 0.50 to 1.00% by mass, P: 0.050% by mass or less, S: 0.050% by mass or less, Cr: 0.80 to 1.30% by mass, Al: 0.01 to 0.10% by mass, The balance is composed of iron and inevitable impurities. The area ratio of pro-eutectoid ferrite is 31% or more and 70% or less, and the steel includes one or more selected from the group consisting of bainite, martensite, and pearlite, Dislocation density is 3.5×10 14 m -2 That's all. Machine structural steel for cold working.

2. 2. The steel for machine structural use for cold working according to claim 1, wherein the pro-eutectoid ferrite has an average crystal grain size of 6 μm or less.

3. Cu: 0.25% by mass or less (excluding 0% by mass), Ni: 0.25% by mass or less (excluding 0% by mass), and The steel for machine structural use for cold working according to claim 1 or 2, further comprising one or more selected from the group consisting of: Mo: 0.40 mass% or less (excluding 0 mass%).

4. Ti: 0.20 mass% or less (excluding 0 mass%) Nb: 0.20% by mass or less (excluding 0% by mass), and The steel for machine structural use for cold working according to any one of claims 1 to 3, further comprising one or more selected from the group consisting of V: ​​1.50 mass% or less (excluding 0 mass%).

5. N: 0.01% by mass or less (excluding 0% by mass), Mg: 0.02% by mass or less (excluding 0% by mass), Ca: 0.05% by mass or less (excluding 0% by mass), Li: 0.02% by mass or less (excluding 0% by mass), and The steel for machine structural use for cold working according to any one of claims 1 to 4, further comprising one or more selected from the group consisting of REM: 0.05 mass% or less (excluding 0 mass%).

6. (a) performing hot working at a working temperature T0 of more than 800 ° C. and not more than 1000 ° C. with a compression ratio of 20% or more; (b) after the step (a), a step of cooling to a first cooling temperature T1 of 670° C. or more and 730° C. or less at a first cooling rate CR1 of 5° C. / sec or more; (c) after the step (b), maintaining the first cooling temperature T1 for a retention time t1 of 10 to 600 seconds; (d) after the step (c), cooling to a second cooling temperature T2 of 550° C. or less at a second cooling rate CR2 of 5° C. / sec or more. The method for producing a steel for machine structural use for cold working according to any one of claims 1 to 5, comprising the steps of:

7. A method for producing a steel wire, comprising subjecting the steel for cold working machine structural use produced by the method according to claim 6 to one or more processes selected from the group consisting of annealing, spheroidizing annealing, wire drawing, heading, and quenching and tempering.

Citation Information

Patent Citations

  • Steel wire rod and bar steel excellent in cold forgeability after spheroidizing and its manufacture

    JP2001089830A

  • Steel wire rod excellent in cold-forgeability after spheroidizing-treatment and producing method therefor

    JP2006225701A

  • High strength cold rolled steel sheet having excellent yield stress, elongation and stretch-flange formability

    JP2009215572A

  • Steel for machine structure for cold working and method of manufacturing the same

    JP2013227602A

  • Steel for cold working machine structures, and method for producing same

    JP2020125538A